2018
DOI: 10.1111/bjd.16127
|View full text |Cite
|
Sign up to set email alerts
|

High plasma 25-hydroxyvitamin D and high risk of nonmelanoma skin cancer: a Mendelian randomization study of 97 849 individuals

Abstract: Genetically determined high 25(OH)D levels did not appear to protect against NMSC, whereas high plasma 25(OH)D concentrations were associated with an observational high risk of NMSC. Thus, the observational association likely reflects confounding by sun exposure rather than causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…It can be challenging to interpret the univariable MR association between 25(OH)D and skin cancers (i.e. melanoma and keratinocyte cancers (KC)) given the potential confounding pathways through pigmentation and skin aging which are established risk factors for these cancers 28 . The univariable MR associations suggest higher 25(OH)D levels increase risk of basal cell carcinoma (BCC) (OR = 1.16 [1.04-1.28], while the OR for melanoma was smaller with confidence intervals overlapping 1 (OR 1.05 [0.90-1.23]).…”
Section: Resultsmentioning
confidence: 99%
“…It can be challenging to interpret the univariable MR association between 25(OH)D and skin cancers (i.e. melanoma and keratinocyte cancers (KC)) given the potential confounding pathways through pigmentation and skin aging which are established risk factors for these cancers 28 . The univariable MR associations suggest higher 25(OH)D levels increase risk of basal cell carcinoma (BCC) (OR = 1.16 [1.04-1.28], while the OR for melanoma was smaller with confidence intervals overlapping 1 (OR 1.05 [0.90-1.23]).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported a RR estimate comparing NMSC risk among those in the highest vs. lowest category of serum/plasma 25(OH)D concentration ( Table 1 ) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Of these, five were conducted in the USA, two in Denmark, and one each in Australia, Brazil, and Poland.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, after adjustment for the effect of possible confounding factors in multivariate logistic regression, vitamin D level could not independently predict the occurrence of SCC. It seems that, as Winsløw et al noted, the level of vitamin D in our population not consuming supplements is a surrogate for their amount of sun exposure, which per se has an established role in skin cancer[20]. Thus this vitamin…”
mentioning
confidence: 70%